A Few Remarks on Wojciech Wrzosek’s Concept of Non-Classical Methodology in Historical Sciences - Dobosz, Artur (Sensus Historiae, 2025)
In this review article, I offer a number of comments and suggestions regarding Wojciech Wrzosek’s article titled “Appendix: The Methodology of Historical Sciences and Metahistory.” For the most part, these are remarks emphasizing the cognitive significance of the Appendix, in which the author opts, within his conception of the methodology of historical sciences, for a discursive intralinguistic concept of truth. Furthermore, I formulate the hypothesis that there is no rigid boundary between the classical concept of the methodology of historical sciences and its non-classical version. This means that a historian, for example, while reading one source material, may spontaneously adopt the classical version of the methodology of the sciences in question, only to, while reading the next material, naturally, imperceptibly embody its non-classical form as defined by Wojciech Wrzosek.